PENGARUH REMUNERASI TERHADAP ETOS KERJA APARATUR SIPIL NEGARA (ASN) PADA KANTOR KEMENTRIAN AGAMA KOTA PEKANBARU TAHUN 2015 - Nadya Rafdiyanti; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
On the expected performance based remuneration program no longer various complaints of public services to the poor performance of reform. Performance based remuneration program will strengthen the mechanisms reward and punishment. Remuneration is given to the officials because employees feel unable to work with peace of mind because the earnings are far from adequate. The allowance for the performance of the employees in the environment ministry of religion is regulated in the Presidential Bylaws the Number 108 Years 2014. The purpose of this research is to know how the impact of remuneration for the work ethos State Civil Apparatus (ASN) at the office of the Ministry of Religion City of Pekanbaru 2015.The type of research that is used in this research is a descriptive research design with associative. The location of this research is the author of the complete in the office of the Ministry of Religion City of Pekanbaru. The number of samples in this research as much as 63 people with sampling techniques in this research is simple random sampling. Data analysis using SPSS statistics tests are simple regression.The hypothesis test results obtained ada influence significant remuneration for work ethos State Civil Apparatus (ASN) at the office of the Ministry of Religion City of Pekanbaru 2015 and test results of the determination coefficient, obtained the value of R2 (R Square) of 0,471. This means that the variables remenureasi effect of 47.1 percent against the work ethos State Civil Apparatus (ASN) at the office of the Ministry of Religion City of Pekanbaru 2015, while the rest of 52.9 percent explained by the other variables is not examined in the model. Suggestions in this research perlu the increased number of remuneration given to state Civil Apparatus, especially the gift of benefits must be adjusted with the workload that must be in the responsibility by the apparatus of the State Civil. In order to State Civil Apparatus felt valued and treated fairly.Key Words : Remuneration, work ethos, Civil Apparatus State, Pekanbaru